Penerapan Metode ELECTRE Dalam Pemilihan Konsultan Perencana Rekayasa - Widjaja, Warkianto (STIKOM Tunas Bangsa Pematangsiantar, 2023)
In the selection of planning consultants, several criteria are used that must be possessed by the assigning company in the bidding process for the selection of the chosen planning consultants. Each company has its own criteria to determine the selected participants as the winners of the planning work auction. The bidding process for planning work is carried out by several companies to determine the most competent planning consultants, resulting in high-quality design processes and outcomes in terms of cost, quality, and time. This research focuses on finding the best alternative using a decision support system based on predetermined criteria using the Electre method. This research is conducted by calculating the values of each criterion for each participating company's alternative in the auction, as well as the weight values for each criterion. Subsequently, a ranking process is carried out to determine the best alternative, which is the selected planning consultant.